2014
DOI: 10.1186/s12888-014-0261-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of socioeconomic deprivation on rate and cause of death in severe mental illness

Abstract: BackgroundSocioeconomic status has important associations with disease-specific mortality in the general population. Although individuals with Severe Mental Illnesses (SMI) experience significant premature mortality, the relationship between socioeconomic status and mortality in this group remains under investigated. We aimed to assess the impact of socioeconomic status on rate and cause of death in individuals with SMI (schizophrenia and bipolar disorder) relative to the local (Glasgow) and wider (Scottish) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 38 publications
(43 reference statements)
5
37
0
1
Order By: Relevance
“…Our findings indicate that, for all mental health disorders, the absolute and relative difference in diabetes rates are exacerbated by increasing level of deprivation, highlighting the additional vulnerability of people with a mental illness who live in deprived areas. Previous Scottish studies have found that the excess mortality associated with severe mental illness is most marked in the most deprived population groups (31), and that multimorbidity, including mental-physical health comorbidity is more prevalent among more deprived groups (32). By demonstrating that the association between mental disorder and type 2 diabetes varies markedly by deprivation level, our study suggests that this increased diabetes risk is due largely to modifiable factors rather than intrinsic physiological effects of the mental illness itself.…”
Section: Interpretation In Context Of Previous Studiessupporting
confidence: 55%
“…Our findings indicate that, for all mental health disorders, the absolute and relative difference in diabetes rates are exacerbated by increasing level of deprivation, highlighting the additional vulnerability of people with a mental illness who live in deprived areas. Previous Scottish studies have found that the excess mortality associated with severe mental illness is most marked in the most deprived population groups (31), and that multimorbidity, including mental-physical health comorbidity is more prevalent among more deprived groups (32). By demonstrating that the association between mental disorder and type 2 diabetes varies markedly by deprivation level, our study suggests that this increased diabetes risk is due largely to modifiable factors rather than intrinsic physiological effects of the mental illness itself.…”
Section: Interpretation In Context Of Previous Studiessupporting
confidence: 55%
“…The SIMD is widely accepted as a means through which scarce government resources can be directed to areas with greatest need across Scotland, and the measure is used extensively in research and audit of health and social care services. While SIMD is the current deprivation measure used in Scotland, there is a suggestion that the broad domains used to measure aspects of the populations health and well‐being are not comprehensive enough (Allik, Brown, Dundas, & Leyland, ; Martin et al., ; Nicholson & Hotchin, ).…”
Section: Methodsmentioning
confidence: 99%
“…Unemployment and alcohol misuse are also common and are related to risk of cardiovascular disease . Importantly, the downward socio‐economic drift often associated with schizophrenia is in itself likely to increase the risk of ill health .…”
Section: Reasons For Excess Mortality and Morbiditymentioning
confidence: 99%